BIMBINGAN DAN KONSELING ISLAM SOLUSI MENJAGA DAN MENINGKATKAN KESEHATAN MENTAL - Maba, Aprezo Pardodi; Hernisawati, Hernisawati; Mukhlishin, Ahmad (JURNAL KONSELING GUSJIGANG, 2017)
Islamic guidance and counseling in Indonesia has existed since first pesantren established, but at that time, had not known the term of “guidance and counseling”. The practice tended to be implicit in many cultural practices which characterized by therapeutic relationship. Along with the inclusion of guidance and counseling in Indonesia, which later developed rapidly, there was arised awareness of the limitations and contradictions of some western approaches to the Islamic values, then the world and Indonesian muslim experts in guidance and counseling began to develop a new approach called Islamic guidance and counseling. Present day, Islamic guidance and counseling has become one of the most effective approaches to alleviate various problems to restore and maintain counselee mental health